Kelayakan Model Bimbingan Kelompok Blended Menggunakan Teknik Restrukturisasi Kognitif Berbasis Nilai-Nilai “Ngudi Kasampurnan”: Systematic Literature Review - Zamroni, Edris; Gudnanto, Gudnanto; Lestari, Indah; Afriliyanto, Agus (Indonesian Journal of Educational Counseling, 2024)
Group guidance is one of the guidance and counseling services in carrying out developmental preventive functions. After the COVID-19 pandemic, the mode of education services has changed significantly, especially with the use of web meeting technology devices as a substitute for direct face-to-face meetings. This research tests the theoretical feasibility of developing a blended group guidance model using cognitive restructuring techniques. This research is library research by exploring research data in the Scopus and Google Scholar databases to find the theoretical feasibility of the model to be developed. The tools used are published or perish, and VosViewer to get an overview of the development potential and academic support expected in developing this blended group guidance model. The results show that 26 studies support the development of a blended group guidance model. However, not all of the research addresses explicitly cognitive restructuring techniques, so this would be a novelty for this research.